NOTES ON THE GENUS CYLINDROCLADIUM (Fungi: Mucedinaceae) - BOEDIJN, K. B.; REITSMA, J. (Research Center for Biology, 1950)
The genus Cylindrocladivm was erected by Morgan in 1892 for a Mucedinaceous fungus with Penicillium-like branching and long,cylindrical,two-celled conidia.The original diagnosis runs: â Cylindrocladium Morgan.